Interpersonal dependency and emotion in every day life - Wang, S.; Roche, M.; Pincus, A.; Conroy, D.; Rebar, Amanda; Ram, N. (Elsevier, 2014)
We expand upon the interpersonal-CAPS framework by examining how dependency moderates the within-person association of interpersonal perceptions and emotions. 184 university students completed a 7-day diary study, reporting on how they perceived their interaction partners and emotions during that interaction. Multilevel regression models were used to examine the associations between interpersonal perceptions and emotions, moderated by interpersonal dependency. For participants with higher dependency, perceiving others as more submissive and unfriendly than usual was associated with decreased positive emotional valance, while perceiving others as dominant and unfriendly in general was associated with less emotional activation. These results are organized using the interpersonal-CAPS framework to articulate dependent personality dynamics, particularly the unique perceptions, expectations, and costs of relying upon unfriendly-dominant others. © 2014.